Identyčnistʹ, (ne)spromožnistʹ ta prynaležnistʹ: liturhija ta pokloninnja krizʹ pryzmu autyzmu = Identity, (Dis)Ability and Belonging: Liturgy and Worship Through the Lens of Autism - Ommen, Armand Léon van (Bogoslovs'ki rozdymi, 2024)
Disabled people often feel excluded from church activities. Focusing on autism, this article explores the problematic, relative absence of autistic people in churches. It will be argued that the concept of normalcy lies at the heart of the problem. Normalcy is understood as the set of dynamics that guard the boundaries of communities, in other words, who does and does not belong. These boundaries are part of what Charles Taylor calls the "framework" of the community, which determines what the community values. This article will argue that those with disabilities easily fall outside of the community’s boundaries. After discussing the dynamics of normalcy, this article offers a theological critique and a proposal for a framework inspired by the Gospel. This enables a "theology of presence" which envisions members of the community being present to each other in a way that reflects the kenosis of Christ.